Radio Komunitas: Media Alternatif Untuk Pemberdayaan Perempuan - MH, Ismahfudi (Musawa Jurnal Studi Gender dan Islam, 2007)
Radio is the most popular medium for communication among common people. It is cheap, yet it is efficient and effective to reach lay communities. It does not require high technology or sophisticated theories, but it has high flexibility to use for interaction among people. The creation of community radio among women will potentially serve their interests for women empowerment, for proliferating justice values and equality, learning democratic practices which use a gender perspective.